The Students’ Ability In Writing Skill: Using Personal Pronoun In Narrative text - Rahmawati Rahmawati; Ernita Fariani Sinaga; Anjelia Saragih; Sukutenta Br Sembiring (Al-Lisan: Jurnal Bahasa, 2021)
This study aims to determine the students’ ability of second grade SMP Talitakum to use personal pronouns in narrative text. The subject of this study are students of second grade and the object of this study was the students' ability to use pronouns in narrative text. The sample of this study are 16 students. Data collection techniques in this study use test and interviews. Based on the data analyzed, the researchers concluded that the students' ability to use pronouns in the narrative text was 68.43% and the students' ability to use personal pronouns in the narrative text is 62.93%. The study concludes that the difficulty affecting students in using pronouns was a lack of understanding of pronouns and narrative text even though they had been taught by the teacher and the lack of grammar books.